Diversity of the Neglected and Underutilized Crop Species of Importance in Benin - A. Dansi; R. Vodouhè; P. Azokpota; H. Yedomonhan; P. Assogba; A. Adjatin; Y. L. Loko; I. Dossou-Aminon; K. Akpagana (The Scientific World Journal)
Many of the plant species that are cultivated for food across the world are neglected and underutilized. To assess their diversity in Benin and identify the priority species and establish their research needs, a survey was conducted in 50 villages distributed throughout the country. The study revealed 41 neglected and underutilized crop species (NUCS) among which 19 were identified as of priority base on 10 criteria among which included their extent and degree of consumption. Reasons for neglect vary with the producers and the agricultural technicians. Market surveys revealed that NUCS are important source of household incomes and substantially contribute to poverty reduction. Review of the literature available revealed that most of the species are rich in nutrients and have some proven medicinal values and the promotion of their use would help in combating malnutrition and improving the health status of the local populations. The knowledge gaps and research needs are immense on most of the species identified as no concrete scientific data is nationally available. In terms of research, almost all has to be done starting from basic ethnobotanical investigation. The results will help the scientists and students willing to conduct research on NUCS in Benin to better orient their research programs.